The motives for teenage girls' use of the Facebook website and the gratifications achieved from it: A Survey Study of a sample of middle school students - Thamer, Alyaa Qasim (Al-Adab Journal, 2021)
The problem of this paper arises in a major question: What are the motives for teenage girls' use of Facebook and the results achieved from it?The aim of this paper is to study the patterns of teenage girls' use of the Facebook, and show their interests and some of their practices .in addition to revealing the motives of teenage girls to use Facebook, and to show what is the benefits that achieved from it. The researcher used the survey method for collecting data, analyzing, and interpreting it. The important results of this paper are: Facebook contributes to influencing on the opinions and thoughts of teenage girls on various dimensions.The use of Facebook leads to the promotion of social integration, by using them own more than one account, and hide their true identity using pseudonyms, allowing them to freely access and communicate with others. in order to avoid the harassment that they may be exposed to, as well as that This indicates negative uses for them by masking their identity.The predominance of ritual motives over utilitarian motives, given the nature of adolescence, whose members tend to achieve entertainment, entertainment and the need to understand the opposite sex, in addition to the utilitarian needs of adolescent girls that focus on creating a social role for them and the pursuit of self-realization by acquiring skills and knowledge that enhance self-confidence Without interfering in their affairs and feeling independent.Facebook achieved emotional and cognitive gratifications, as the gratifications achieved by adolescent girls varied between entertainment and entertainment that came in the forefront, gaining information and experiences, relieving psychological pressure, as well as raising the cultural level, forming relationships with the opposite sex, and feeling trust and freedom of expression